Investigating relationships with alcohol: the construction of meaning through narrative in interview situations - Good, Adrian Brinton (2013)
Relationships between humans are comprised of many interwoven facets. So are relationships between humans and alcohol. This pilot research project attempts to conceptualize a few of the components that exist in the latter relationship and demonstrate an approach that may be used for additional investigation in the future. Ten male college students discussed their history with alcohol in an interview setting and, in doing so, described ways in which they developed relationships with the substance. Discussion of familial socialization focused on lessons centered on culture and/or moderation. Informants embedded discussion of the continued development of these relationships in discussion with components they considered to be important to their life stories. Much of the language used to put words around these relationships was divided into vernaculars of intent and vernaculars of strategy. These groupings allow for a rich understanding of different motivations that rest behind alcohol-related decisions and ways people categorize and understand different types of drinking behavior. Structuring the data in this manner creates an understanding of different alcohol-related desires and a variety of drinking styles that people use to achieve these ends. As alcohol can impact a situation in unpredictable ways, attempts to match strategy with intent may fail. Some of these strategies, such as alcoholic drinking, were not described in a favorable manner. With this in mind, a struggle for control is embedded in the vernaculars of strategy. By doing this, informants projected agency and power on alcohol, thereby making it a subject and creating a viable relationship partner. This battle was also evident in the narratives told by informants. Some told of the ability to maintain control over alcohol throughout the life span up to that point. Others reported periods where control was lost and described the personal and social process through which it was regained. At the time of the interview, each person stated that he was reliably in command of his interactions with alcohol